Narrative expressions of university students. Emotional and academic situation during confinement - Feria-Cuevas, Yolanda; López López, Cinthya Araceli; Núñez Hernández, Alfonsina; Mora Núñez, Margarito (Emerging Trends in Education, 2026)
According to UNESCO (2020), the most immediate impact of the COVID-19 pandemic on higher education students was the temporary cessation of face-to-face activities at Higher Education Institutions (HEIs). This caused uncertainty, impacts on the emotional situation, financial burdens and, of course, the continuity of learning. The purpose of this work was to understand the perception of students regarding their emotional and academic situation in the pandemic scenario and how they perceived the role of teachers as facilitators of learning. The project design was mixed, that is, a quantitative and qualitative analysis was proposed. For this purpose, a questionnaire was sent with questions in Likert format and with open questions. The results showed that most of the participants experienced negative feelings, spent between two and four hours a day receiving online classes, usually from their cell phone, and reported that the biggest problems were distractions and failures in the internet connection. It is concluded that in general students prefer in-person classes to virtual classes because they avoid distractions and, above all, have the opportunity to socialize. In addition, they consider that they perform better and their education is more solid and comprehensive
Keywords: Text analysis; narrative; emotional state; academic perception; health emergency